Molecular evidence of recent hybridization between eastern and western populations of a whitefly species on cassava in the Democratic Republic of the Congo: A potential threat to the spread of cassava brown streak disease - Olivier Likiti Kola; Christophe Simiand; Hadija Mussa Ally; Sharon L. van Brunschot; Justin S. Pita; John Colvin; Godefroid Monde Te Kazangba; Hélène Delatte (PLoS ONE, 2026)
Cassava mosaic disease (CMD) and cassava brown streak disease (CBSD) are two viral diseases that threaten cassava production in the East and Central African countries. These diseases are spread by members of the cryptic species complex of the whitefly Bemisia tabaci sensu lato, and/or through the propagation of infected stem cuttings. This study aims to i) identify the B. tabaci s.l. species colonizing cassava in the north of the Democratic Republic of the Congo (DRC), ii) analyse their genetic diversity, and iii) examine how this diversity is geographically structured or influenced by invasions from neighbouring (eastern) countries with high CBSD prevalence. A comprehensive sampling survey was conducted across 43 sites from east to west in the DRC, spanning 1339 km. Both nuclear and mitochondrial markers were used to identify the species and study the genetic diversity and structuring of the populations. Three species of B. tabaci s.l. were found: B. tabaci SSA1-SG1 U SG2; B. tabaci SSA1-SG3, and B. tabaci SSA2 U SSA3. In the surveyed provinces, B. tabaci SSA1 SG1 U SG2 was the dominant species (94.91%). It was structured into two genetic clusters along the east-west transect, while B. tabaci SSA2 U SSA3 was restricted to the western provinces. The findings of this study confirm that B. tabaci SSA1-SG1 U SG2 is the most abundant and adapted species on cassava in the DRC. It is likely that this species is responsible for the spread of cassava virus diseases in the DRC. Furthermore, the results showed significant geographical structuring of B. tabaci SSA1-SG1 U SG2 populations, with potential movements of populations towards the west of the country. This highlights the increased risk of virus spread towards West Africa.